First Field-Based Evidence That the Seagrass-Lucinid Mutualism Can Mitigate Sulfide Stress in Seagrasses - van der Geest, Matthijs; van der Heide, Tjisse; Holmer, Marianne; de Wit, Rutger (Frontiers in Marine Science, 2020)
Seagrass meadows form vital ecological components of coastal zones worldwide, but are rapidly declining. Large-scale seagrass diebacks have been related to accumulation of toxic sulfide in the sediment, a phenomenon predicted to occur more frequently in the near future due to ongoing global warming and increasing organic loading of coastal systems worldwide. Recently, a facultative mutualism between seagrasses and lucinid bivalves with endosymbiotic sulfide-consuming gill bacteria was discovered that may prevent toxic sulfide accumulation in seagrass sediments. Yet, direct field-based evidence for the importance of this mutualism in alleviating sulfide stress in seagrasses is currently lacking, as well as how its role may change when sediment sulfide levels increase due to environmental change. Here, we investigated the sulfide detoxification function of this seagrass-lucinid mutualism and its resilience to organic-loading induced sulfide stress in a temperate lagoon system (Thau lagoon, France), using a correlative field survey and a full factorial field experiment. The field survey revealed a strong positive correlation between seagrass above-ground biomass and lucinid densities, and pore water sulfide concentrations close to zero at all sites. Furthermore, the field experiment demonstrated that addition of organic matter increased sedimentary sulfide intrusion in seagrass (Zostera noltei) leaves (a proxy for sulfide stress) by 21%, while experimentally enhanced lucinid densities counteracted 59% of this enhanced sulfide intrusion. Moreover, addition of organic matter reduced rhizome biomass and considerably increased lucinid condition (expressed as flesh/shell dry weight ratio), lucinid tissue sulfur content, and total lucinid biomass. These results provide the first field-based evidence that the seagrass-lucinid mutualism mitigates sulfide stress in seagrasses, and suggest that the dependence of seagrass on this mutualism will increase under conditions of enhanced sediment sulfide production, as predicted for the near future. Therefore, we suggest that awareness of the importance of the seagrass-lucinid mutualism for seagrass ecosystem functioning may be instrumental for designing new measures for improving long-term restoration success and seagrass resilience to global change.